Doping, kaj je to in kdaj? - Osredkar, Joško (Medicinski razgledi, 2003)
Doping involves the use of substances and methods prohibited by international and national sports institutions. The use of certain substances and methods isharmful to the human body, therefore all sports organizations are trying to protect athletes from the harmful side effects of such substances and methods.The article discusses individual classes of prohibited substances, including stimulants, narcotics, anabolic agents, diuretics, peptide hormones and their analogues, blood doping, alcohol, marihuana, local anesthetics, corticosteroids and beta-blockers. A broader view on doping in sports is presented, as well as regulations on doping. The current list of prohibited substances and methods is added as well.
Keywords: Doping In Sports; Doping v športu; Hrana, dodatki; Sports; Legislation And Jurisprudence; Nedovoljene snovi; Psihotropna zdravila; Psychotropic Drugs; Street Drugs; Športi; Food Additives; Alkohol, pitje; Aminokisline; Receptors, Peptide; Anabolni steroidi; Central Nervous System Stimulants; Analgetiki opioidni; Amino Acids; Cardiotonic Agents; Centralno živčevje, stimulansi; Diuretiki; Analgesics, Opioid; Anabolic Steroids; Kardiotoniki; Diuretics; Receptorji peptidni; sport; šport; Alcohol Drinking; doping; prepovedane substance; zakonodaja